Graft versus Host Disease: From Basic Pathogenic Principles to DNA Damage Response and Cellular Senescence. (26th March 2018) - Kuba, Adam; Raida, Ludek
Abstract : Graft versus host disease (GVHD), a severe immunogenic complication of allogeneic hematopoietic stem cell transplantation (HSCT), represents the most frequent cause of transplant-related mortality (TRM). Despite a huge progress in HSCT techniques and posttransplant care, GVHD remains a significant obstacle in successful HSCT outcome. This review presents a complex summary of GVHD pathogenesis with focus on references considering basic biological processes such as DNA damage response and cellular senescence.